(untitled) (KULT_online, 2010)
The Metzler Lexikon DDR-Literatur (Metzler’s Lexicon of GDR Literature) successfully delivers widely diversified information about all areas of literary life in the GDR without carrying out ideological evaluations. The encyclopeadia not only presents authors of and from the GDR, but gives insight into central topics and genres, important cultural and political events, influential anthologies and magazines, different aspects of literary life and to the fatal combination of intellect and power. It combines various positions and thereby consciously keeps the term ’GDR literature’ open.